ANALISIS PERUBAHAN PENDAPATAN PT TELEKOMUNIKASI INDONESIA TBK. TAHUN 2017 DAN 2018 - Suasri, Eni; Dahlia, Dahlia (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2020)
This study aims to analyze the comparison of the ups and downs of a financial statement that occurred at PT Telekomunikasi Indonesia Tbk. during 2017 and 2018. Data was obtained from the Indonesia Stock Exchange (IDX) and then analyzed using income change methods againt gross profit analysis.. From the results of the study note that the financial company PT Telekomunikasi Indonesia Tbk. over the past two years it has tend to decline. The decline was due to the sales faktor which had a smaller value than the change in gross profit due to higher competition and the increasing number of similar business actors in the telecommunications industry which resulted in increased activity, advertising, price reduction and the emergence of various services offered by operators. Analysis of financial statements can provide a clear picture of the financial condition and results of operations of the company, the information can be used in making a business and investment decision.